Mothers and daughters in nineteenth-century America : the biosocial construction of femininity - Theriot, Nancy M. (The University Press of Kentucky, 2015)
The feminine script of early nineteenth century centered on women's role as patient, long-suffering mothers. By mid-century, however, their daughters faced a world very different in social and economic options and in the physical experiences surrounding their bodies. In this groundbreaking study, Nancy Theriot turns to social and medical history, developmental psychology, and feminist theory to explain the fundamental shift in women's concepts of femininity and gender identity during the course of the century -- from an ideal suffering womanhood to emphasis on female control of physical self.